MERANTAU: SEBUAH PILIHAN ATAU KETERPAKSAAN? STUDI SUPIR ANGKUTAN KOTA PERANTAU BATAK ANGKOLA-MANDAILING DI KOTA BANDUNG - Azhar Riyadi (UIN Fatmawati Sukarno Bengkulu, 2019)
Merantau: A Choice or Force? A Study of the Anggola-Mandailing Batak City Transport Driver in the City of Bandung. Life in the world of overseas certainly requires a lot of adaptation, especially regarding differences in cultural background. As a Batak Angkola-Mandailing certainly faces the issue of identity as a Batak who must be able to adapt to the dominant Sundanese culture in the city of Bandung. As a Batak, even though living abroad is still bound by the social system rather than with little concession. Choosing as a driver is the most possible choice because social networks are more likely. Life as a nomads is not the final choice but as a choice between, although not a few are also resigned because it is difficult to return to the area of origin.